Small One-Helix Proteins Are Essential for Photosynthesis in Arabidopsis - Beck, Jochen; Lohscheider, Jens N.; Albert, Susanne; Andersson, Ulrica; Mendgen, Kurt W.; Rojas-Stütz, Marc C.; Adamska, Iwona; Funck, Dietmar (Frontiers in Plant Science, 2017)
The extended superfamily of chlorophyll a/b binding proteins comprises the Light-Harvesting Complex Proteins (LHCs), the Early Light-Induced Proteins (ELIPs) and the Photosystem II Subunit S (PSBS). The proteins of the ELIP family were proposed to function in photoprotection or assembly of thylakoid pigment-protein complexes and are further divided into subgroups with one to three transmembrane helices. Two small One-Helix Proteins (OHPs) are expressed constitutively in green plant tissues and their levels increase in response to light stress. In this study, we show that OHP1 and OHP2 are highly conserved in photosynthetic eukaryotes, but have probably evolved independently and have distinct functions in Arabidopsis. Mutations in OHP1 or OHP2 caused severe growth deficits, reduced pigmentation and disturbed thylakoid architecture. Surprisingly, the expression of OHP2 was severely reduced in ohp1 T-DNA insertion mutants and vice versa. In both ohp1 and ohp2 mutants, the levels of numerous photosystem components were strongly reduced and photosynthetic electron transport was almost undetectable. Accordingly, ohp1 and ohp2 mutants were dependent on external organic carbon sources for growth and did not produce seeds. Interestingly, the induction of ELIP1 expression and Cu/Zn superoxide dismutase activity in low light conditions indicated that ohp1 mutants constantly suffer from photo-oxidative stress. Based on these data, we propose that OHP1 and OHP2 play an essential role in the assembly or stabilization of photosynthetic pigment-protein complexes, especially photosystem reaction centers, in the thylakoid membrane.